Supervision Efforts to Improve the Performance of Social Studies Subject Teachers During the Covid 19 Pandemic - Sari, Tri Novita; Boussanlègue, TCHABLE (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
The purpose of this research is to identify the reasons of issues encountered by instructors and efforts to address them through monitoring of social studies learning activities. This study is an example of descriptive qualitative research. The interview approach was employed to collect data in this study. Purposive sampling was employed to acquire data from the Social Studies teacher at MTs Negeri 1 Prabumulih in this study. The findings of the supervision implementation showed that efforts may be made to improve teacher performance by offering training and updating learning plans that respond to students' conditions and situations during the covid 19 pandemic. As a result of changes in the atmosphere and learning environment, student motivation in participation in learning grows. With comparison to before the epidemic. This research was also only undertaken at Madrasahs in Prabumulih City, and it was never conducted to the field of social sciences studies. This study helps the madrasa principal by providing stimulation in the form of criticism and incentive to instructors in an effort to enhance performance.